Trade and Unemployment in Germany: An Empirical Exploration and Some Theory - Martin Klein; Tobias Weirowski (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
This paper investigates the link between unemployment and external trade in Germany, using data on unemployment, international trade and economic activity for the 16 German federal states (Länder). With panel data econometrics we show that international trade as measured by state-wise trade shares have a significant negative impact on state-wise unemployment rates. We discuss to what extent this reflects mercantilist tendencies embedded in the political economy of the Federal Republic. There is no clear evidence in favor of simple mercantilism. We suggest three alternative explanations, linked to the structural rigidities of the German labor market, government involvement in the education and training system and certain labor market policies which provide government-subsidized unemployment insurance benefitting (mainly) export industries.
urn:nbn:de:gbv:27-20131119-144153-6
Keywords: F14; F15; O50; 330; International trade; panel study; Arbeitslosigkeit; Internationale Wirtschaft; Teilstaat; Panelforschung; Schätzung; Deutschland